Comparative Analysis of Conservative Values in Perempuan Berkalung Sorban (2009) and Mona Lisa Smile (2003) - Weni Ratminingsih; Harsiwi Fajar Sari (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
Tradition cannot be separated from human life, in any form it is, depending on its culture and community. In the society, there are people who intend to preserve it, or to change it. Conservatism itself is referred to maintain what is already put in place in the society. This is found in movies namely Mona Lisa Smile and Perempuan Berkalung Sorban. This study aims to analyze how the characters in both movies manifest the conservatism ideas. The research uses the theory of Conservatism by John Kekes. The qualitative descriptive method is used, and the primary data is from the dialogues of the characters. The secondary data of other information related is also used. The result shows that the characters in both movies portray the four ideas offered by John Kekes about Conservatism, namely Skepticism, Pluralism, Traditionalism, and Pessimism. Further, being conservative to the tradition as shown by the characters in the movies is worth preserved.